2023
DOI: 10.3390/biomedicines11030745
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Behaviors and Degradation Properties of Multilayered Polymer Scaffolds: The Phase Space Method for Bile Duct Design and Bioengineering

Abstract: This article reports the electrospinning technique for the manufacturing of multilayered scaffolds for bile duct tissue engineering based on an inner layer of polycaprolactone (PCL) and an outer layer either of a copolymer of D,L-lactide and glycolide (PLGA) or a copolymer of L-lactide and ε-caprolactone (PLCL). A study of the degradation properties of separate polymers showed that flat PCL samples exhibited the highest resistance to hydrolysis in comparison with PLGA and PLCL. Irrespective of the liquid-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…More proline and hydroxyproline increased the thermal stability of collagen because of a higher density of crosslinks [ 30 ], which can also be improved by chitin nanofibers for the usage as scaffolds and wound-dressing materials [ 31 ]. Klabukov et al [ 32 ] found that the copolymer had a higher stability and the ability to resist hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…More proline and hydroxyproline increased the thermal stability of collagen because of a higher density of crosslinks [ 30 ], which can also be improved by chitin nanofibers for the usage as scaffolds and wound-dressing materials [ 31 ]. Klabukov et al [ 32 ] found that the copolymer had a higher stability and the ability to resist hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…While with respect to inadequate mechanical strength, the incorporation of the inorganic phase with electrospun materials and postprocessing modification are the best methods to overcome this limitation, as doing so can fabricate electrospun scaffolds with increased structural and mechanical strength [40]. Furthermore, several experiments have been conducted to produce multilayered and heterogeneous scaffolds with predictable mechanical properties [92,93].…”
Section: Solution For Overcoming the Electrospun Scaffold Limitationmentioning
confidence: 99%
“…To ensure the integrity of the regional tissue microenvironment, the mechanical properties of engineered scaffolds must match the normal tissue morphogenesis [ 96 ]. The stiffness of the brain tissue is usually used as a yardstick when discussing mechanical mismatch between engineered biomaterials and brain tissue.…”
Section: Release Kinetics Of Electrospun Nanofibres Is Dependent On P...mentioning
confidence: 99%